Learners’ perspective of using 360-degree video in reading classroom - Siti Norzaimalina, Abd Majid; Rosnani, Ismail; Aisyah Hanum, Abu Bakar (Secholian Publication PLT, 2020)
The use of technology is so diversified and adaptable to various kinds of field including mastering English language skills. In numerous studies, technology has shown that it contributes to improve their language mastery, increase motivation, and promote better comprehension. Since we are moving from IR 3.0 to IR 4.0, it is good to keep up with the current trend in technology and use it for the students’ benefits. One of the technologies is virtual reality which includes the use of 360-degree video. This 360-degree video offers omnidirectional perspective and give almost realistic experience to learners especially when using together with head-mounted device. This type of video exposes students to a new learning experience that is different from watching video on the screen. Therefore, this study aims to uncover learners’ perspectives about the advantages and disadvantages of using 360-degree video in the reading classroom.